STUDENT ENGAGEMENT IN LEARNING LISTENING HELP MOVIE ONLINE DURING THE COVID-19 PANDEMIC - Febryna Alawiyah Tanjung; Totoh Tauhidin Aba (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
The reason of this think about was to discover out whether English-language film media was fitting to utilize in online tuning in learning within the middle of the covid-19 widespread and how the understudies reacted to the connected film media. The film utilized in this investigate is within the frame of a life activity entitled The Lion King which tells almost the battle for control of the lion kingdom. The strategy utilized is expressive subjective strategy. From the comes about of perceptions utilizing surveys and Questions Answers conducted on six understudies of SMP Negeri 1 Kotabaru, it was found that film media was suitable to utilize in tuning in learning and the students' reactions were that understudies were interested and got to be excited in learning tuning in and lexicon with English film media.